Peer Violence – Bullying Among High School Students - Gojković, Vesna; Vukičević, Leposava (Zbornik Instituta za kriminološka i sociološka istraživanja, 2011)
Bullying (Eng. bullying) refers to any form of violence, physical or mental. The problem of this study was to examine the relationship between the disciplinary orientation, educational style of parents and exposure to peer violence on the occurrence of aggression, or bullying among young people in high schools. Except the detection of hypothetical relations, the aim was to contribute to the development of educational and therapeutic programs in working with adolescents, both with those who commit violence, and those who suffer. The research included 200 high school students living in Belgrade, both males and females, aged between 15 and 19 years. Measuring instruments used in this research were made by the author of this research for the purpose of the research. Data were statistically analyzed using factor analysis, and then extracted factors were correlated with Pearson's model. The obtained results have proven that there is a high degree of physical and verbal violence among high school students, also that physical violence is mostly done by boys and verbal and social violence by girls. It was found that violent behavior is in significant correlation with previous victimization. Also, the affective component is more important for forming violent identity than behavioral, and that the effects of punishment and lack of gratification have a similar effect. Disciplinary actions at school are correlated with verbal and social violence, but not with physical violence.